Coconut and durian skin peelers machine / Akmal Danial Mohd Asri and Norjasween Abdul Malik - Mohd Asri, Akmal Danial; Abdul Malik, Norjasween (School of Mechanical Engineering, 2023)
Durian and coconut are widely recognized as popular fruits in Malaysia, but peeling their skins can be a time-consuming task. Recognizing the challenges faced in peeling coconut and durian skins, this project aims to fabricate a machine specifically designed to peel off the skin easily and safely, surpassing the traditional methods. The primary focus of this project is to design, analyze, and fabricate a coconut and durian skin peeler machine that prioritizes safety, user-friendliness, and energy efficiency. The product incorporates a lever mechanism, consisting of a spring and an L-shaped stainless-steel component. It has compact dimensions of 400mm x 400mm x 300mm and is lightweight, making it portable. In conclusion, the fabrication of this product has been successfully accomplished, and it performs effectively. Results from product testing indicate that peeling the skin of a coconut requires at least 100N of human strength using this machine, taking approximately 150 seconds. Similarly, peeling the skin of a durian necessitates a minimum of 120N of human strength within approximately 180 seconds. This coconut and durian skin peeler machine is expected to benefit lower-income farmers and families, as it will be available at an affordable price